Technical Update on MR Neurography - Martín-Noguerol, Teodoro; Montesinos, Paula; Hassankhani, Alvand; Bencardino, Dario A.; Barousse, Rafael; Luna, Antonio (Seminars in Musculoskeletal Radiology, 2022)
Imaging evaluation of peripheral nerves (PNs) is challenging. Magnetic resonance imaging (MRI) and ultrasonography are the modalities of choice in the imaging assessment of PNs. Both conventional MRI pulse sequences and advanced techniques have important roles. Routine MR sequences are the workhorse, with the main goal to provide superb anatomical definition and identify focal or diffuse nerve T2 signal abnormalities. Selective techniques, such as three-dimensional (3D) cranial nerve imaging (CRANI) or 3D NerveVIEW, allow for a more detailed evaluation of normal and pathologic states. These conventional pulse sequences have a limited role in the comprehensive assessment of pathophysiologic and ultrastructural abnormalities of PNs. Advanced functional MR neurography sequences, such as diffusion tensor imaging tractography or T2 mapping, provide useful and robust quantitative parameters that can be useful in the assessment of PNs on a microscopic level. This article offers an overview of various technical parameters, pulse sequences, and protocols available in the imaging of PNs and provides tips on avoiding potential pitfalls.
Keywords: peripheral nerve; neurography; magnetic resonance imaging